Pemberdayaan Anak Panti Asuhan Murni Kota Makassar Melalui Literasi Membaca - Nona Merry M. Mitan; Oktaviani Wulandari; Ridha Amalia; Nurul Aulia; Arliani Sukma; Agung Nugroho (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to increase the reading interest of the Murni Orphanage children through the Literacy Diary method. The method of implementing this service used mentoring by implementing reading activities for 15 minutes every day and writing down the results of the reading in a Literacy Diary. Questionnaires were used to evaluate this activity, and the results were analyzed descriptively. The results of this community service activity could increase children's interest in reading, with a satisfaction level of 77.8% of the usefulness indicator for activity participants. The indicators of the success of this service also included the equipment used during the activity, the atmosphere and situation during the implementation of the activity, activity time, the media, reading materials/materials, guidance from a mentor, reading literacy practices, mentor's adaptability, and mastery of the material from the mentor respectively.